ZMK1 Is Involved in K+ Uptake and Regulated by Protein Kinase ZmCIPK23 in Zea mays - Han, Wu; Ji, Yun; Wu, Wei; Wu, Wei-Hua; Feng, Han-Qian; Wang, Yi (Frontiers in Plant Science, 2021)
Potassium (K+) is one of essential mineral elements for plant growth and development. K+ channels, especially AKT1-like channels, play crucial roles in K+ uptake in plant roots. Maize is one of important crops, however the K+ uptake mechanism in maize is little known. Here we report the physiological functions of K+ channel ZMK1 in K+ uptake and homeostasis in maize. ZMK1 is a homolog of Arabidopsis AKT1 channel in maize, and mainly expressed in maize root. Yeast complementation experiments and electrophysiological characterization in Xenopus oocytes indicated that ZMK1 could mediate K+ uptake. ZMK1 rescued the low-K+-sensitive phenotype of akt1 mutant and enhanced K+ uptake in Arabidopsis. Overexpression of ZMK1 also significantly increased K+ uptake activity in maize, but led to an oversensitive phenotype. Similar to AKT1 regulation, the protein kinase ZmCIPK23 interacted with ZMK1 and phosphorylated the cytosolic region of ZMK1, activating ZMK1-mediated K+ uptake. ZmCIPK23 could also complement the low-K+-sensitive phenotype of Arabidopsis cipk23/lks1 mutant. These findings demonstrate that ZMK1 together with ZmCIPK23 plays important roles in K+ uptake and homeostasis in maize.